New Iterative Method: An Application for Solving Fractional Physical Differential Equations - A. A. Hemeda (Abstract and Applied Analysis)
The new iterative method with a powerful algorithm is developed for the solution of linear and nonlinear ordinary and partial differential equations of fractional order as well. The analysis is accompanied by numerical examples where this method, in solving them, is used without linearization or small perturbation which confirm the power, accuracy, and simplicity of the given method compared with some of the other methods.